Radon and magnetic anomalies in the territory of the city Kyiv: environmental aspect - М.І. Орлюк; І.І. Онищук; А.О. Роменець; А.В. Марченко; П.О. Яцевський; І.М. Орлюк (Геофизический журнал, 2021)
Magnetic and radon anomalous fields are essential geophysical entities of environment which determine to a considerable degree its ecological state. Revelation of magnetic and radon anomalous zones is an urgent task for the studies of geo-environmental state of the territory and appraisal of its ecological safety. The greatest danger is produced by the areas where the faults are localized with radon anomalies related in the upper part of the Earth crust. For the territory of Kyiv geological characteristics of the studied area has been reviewd, schemes of regional and accompanying faults have been adjusted and completed, maps of module and anomalies of module of geomagnetic field induction as well as a scheme of radon anomalies in water and subsoil air have been elaborated. Connection between radon anomalies with faults and natural magnetic fields has been shown which consisted in correlation of radon anomalies with negative and small positive values of anomalous magnetic field and related to thick zones of fracturing with active fluidal-dynamic activity and the faults of diagonal and orthogonal systems being the zones of radon emanation into atmosphere. Radon anomalies in subsoil air are mainly controlled by Irpin-Borshchagivka, Pushcha-Vodytsya, Kyiv and Darnytsya faults of northwestern-northern strike and Petrivka-Pukhivka and Glevakha-Brovary faults of northwestern strike. For some stations of Kyiv metro the excess of environmental norms of magnetic field and radon anomalies has been determined which can be explained by constructive features of metro compartments and their location in fault zones. It has been shown that radon anomalies are spatially and temporally stabile and magnetic anomalies, especially in metro, are characterized by considerable changes of magnetic field in both low-frequency and high-frequency spectra of their variation.